Disaster preparedness behaviors in biology education: Knowledge of environmental disaster mitigation - Lufty Hari Susanto; Rita Istiana; Rita Retnowati; Ekamilasari; Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Md. Mehadi Rahman4; R. Udhaya Mohan Babu; Rahmawati Darussyamsu; Ainur Rosyid (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
Environmental disaster was important issue to be solved. Current situation disasters such as flood, earthquake, tsunami, volcanoes and others could be happened. This study aimed to obtain information about the relationship between knowledge of disaster and preparedness behaviors and disaster preparedness behaviors. This research was a Sequential Explanatory combination research consisting of 2 variables, namely knowledge about disaster mitigation as an independent variable (X) and disaster preparedness behaviors as a dependent variable (Y). This research was conducted in January-June 2019. The population in this study was all students of Grade XI MIPA in MAN in Bogor City in the academic year 2018/2019 with a total sample of 207 respondents. Research data were obtained using multiple choice test and observation sheet. Quantitative data analysis with descriptive statistical calculations, prerequisite tests using the Liliefors test and the Bartlett test. The data hypotheses testing used the Pearson Product Moment formula. Analysis of qualitative data carried out by reducing data, presenting data, and drawing conclusions. The results showed that there was a positive relationship between knowledge of disaster mitigation and disaster preparedness behaviors (t-value 3.56 > t-statistic 0.05, r=0.234 & r2=5.51%) with a low interpretation value. The conclusion of this research there were low relationship between knowledge of disaster and preparedness behaviors.